CONSTITUTIONAL MORALITY: BALANCING DEMOCRATIC VALUES AND JUDICIAL ETHICS IN A MODERN STATE - Awasthi, Aparna; Verma , Rajesh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Constitutional morality serves as a fundamental principle in modern democratic states, ensuring that governance operates within ethical and Constitutional boundaries. This research paper explores the intricate relationship between Democratic values—such as majority rule, individual rights, and public participation—and Judicial ethics, which emphasize independence, impartiality, and Constitutional supremacy. While Courts play a crucial role in upholding Constitutional morality, challenges such as Judicial overreach, political influence, majoritarian pressures, and lack of Judicial accountability often create tensions between Democracy and Judicial integrity. By analysing global perspectives and the Indian context, this paper highlights the evolving role of Constitutional morality in maintaining the delicate balance between law and democracy. The study concludes with recommendations for enhancing Judicial transparency, ethical accountability, and democratic governance, ensuring that Constitutional morality continues to serve as a guiding force for justice and equality in a modern state.